REVIEW OF A REFUSAL TO GRANT A PROSPECTING RIGHT Global Pact Trading 207 (Pty) Ltd v The Minister of Minerals and Energy; The Regional Manager: Minerals and Energy, Free State Region; The Deputy Director-General: Minerals and Energy (Case Nr 3118/2006 (O) - PJ Badenhorst; Marita Carnelley (Obiter, 2022)
The decision involved an application for the review and setting aside of a refusal to grant a prospecting right in terms of section 17 of the Mineral and Petroleum Resources Development Act 28 of 2002 (the “MPRD Act”)(par 1). The decision also dealt with the right (and duty) of an applicant to an internal appeal in terms of section 96 of the MPRD Act (par 5) as well as the procedural fairness of the decision (par18). The decision by the state to refuse the application for a prospecting right was reviewed and set aside by the court, without requiring such internal appeal, (par 20) as the decision was regarded as manifestly unfair (par 18). The court referred the matter back to the Minister for reconsideration (par 18). At the outset some background information is provided. The idea is not toprovide a detailed discussion about the application for a prospecting right.Thereupon the facts of the case and decision are dealt with and discussed.